A Conceptual Model for the Evaluation of Financial Sustainability - İbrahim Can; Refika Bakoğlu (Istanbul Management Journal)
The primary aim of this research is to propose a framework and model for the evaluation of financial sustainability. To allow companies’ evaluation of financial sustainability, the proposed model identified financial assurance considerations. This scope includes profitability, cash generation, and enterprise value indicators used to measure financial data in the years 2008–2017 for five major companies represented in the Sustainability Index with a combined 41.9% share in the Istanbul Stock Exchange’s market value. The findings indicate that the upper limits representing financial performance effectively reflected financial sustainability assurance as an indicator of cash generation, revealing KCHOL, at 79.45 points,ranking advanced; SAHOL, at 67.75 points, and THYAO, at 61.47 points, ranking strong; whereas ISCTR, at 40.57 points, and TCELL at 34.20 points, both ranked as limited for financial sustainability assurance and evaluation.